A clinical tool to measure plagiocephaly in infants using a flexicurve: a reliability study - Leung A; Watter P; Gavranich J (Dove Medical Press, 2013)
Amy Leung,1 Pauline Watter,2 John Gavranich3 1Department of Physiotherapy, Royal Children's Hospital, Brisbane, Australia; 2Physiotherapy Division, University of Queensland, Brisbane, Australia; 3Child and Family Health Services, West Moreton Health Service District, Ipswich, Australia Purpose: There has been an increasing incidence of infants presenting with plagiocephaly in the last two decades. A practical, economical, and reliable clinical plagiocephaly measure is essential to assess progression and intervention outcomes. This study investigated the reliability of a modified cranial vault asymmetry index using a flexible curve in infants. Measurement: A flexicurve was molded to the infant's head and its shape maintained as it was placed onto paper to trace the head shape. Using a small modification of Loveday and De Chaplain's procedure to measure a cranial vault asymmetry index, a pair of diagonals were drawn at 30° through the midpoint of the central line to their intersection with the traced head outline. The difference in length of the paired diagonals was divided by the short diameter then multiplied by 100%, yielding the modified cranial vault-asymmetry index. Patients and methods: Infants referred to a community health physiotherapist for assessment due to suspected abnormal head shape were included. To explore intrarater reliability, 34 infants aged 3–14 months were measured twice (T1/T1′) at the beginning, and 21 of these remeasured twice at the end (T2/T2′) of their physiotherapy sessions. Test–retest reliability used matched-average data (T1/T1′) and (T2/T2′) from 21 infants. To explore interrater reliability, 18 healthy infants aged 2–6 months were recruited. Each infant was measured once by each rater. Results: For intrarater reliability, the intraclass correlation coefficient with 54 degrees of freedom (ICCdf54) was 0.868 (95% confidence interval [CI] 0.783–0.921); for test–retest reliability, ICCdf20 = 0.958 (95% CI 0.897–0.983); and for interrater reliability, ICCdf17 = 0.874 (95% CI 0.696–0.951). Conclusion: The modified cranial vault asymmetry index using flexicurve in measuring plagiocephaly is a reliable assessment tool. It is economical and efficient for use in clinical settings. Keywords: plagiocephaly, modified cranial vault asymmetry index, infant, community health, reliability